PJMHS 2021
DOI: 10.53350/pjmhs211571578
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal oral health with early childhood caries among rural areas of Punjab

Abstract: Aim: To explore the relationship between oral health status of mothers and caries prevalence of caries among their children in rural areas of Pakistan. Methodology: This crossectional study was conducted in 9 rural health centers of Punjab, Pakistan. Purposive convenient sampling was used to collect data. Sample size was 500 mothers with their children. Results: Socioeconomic status of family as well as the purpose for the last visit at dental hospital for the treatment of child were found positively linked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, living in a deprived neighborhood is strongly associated with early childhood caries, pointing to the importance of community and environmental factors [ 7 ]. Maternal oral health is positively linked with the socioeconomic status of the family, affecting caries prevalence in children [ 23 ]. A notable study by Dr. Eman Bakhurji et al in 2020 on Saudi male teenagers found that the use of fluoride toothpaste was associated with lower odds of caries, especially in less advantaged socioeconomic groups, emphasizing the importance of simple oral health practices in mitigating the impact of socioeconomic disparities on dental health [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, living in a deprived neighborhood is strongly associated with early childhood caries, pointing to the importance of community and environmental factors [ 7 ]. Maternal oral health is positively linked with the socioeconomic status of the family, affecting caries prevalence in children [ 23 ]. A notable study by Dr. Eman Bakhurji et al in 2020 on Saudi male teenagers found that the use of fluoride toothpaste was associated with lower odds of caries, especially in less advantaged socioeconomic groups, emphasizing the importance of simple oral health practices in mitigating the impact of socioeconomic disparities on dental health [ 24 ].…”
Section: Reviewmentioning
confidence: 99%